Elucidating the role of key physio-biochemical traits and molecular network conferring heat stress tolerance in cucumber - Hongal, Dhananjay A.; Raju, Dhandapani; Kumar, Sudhir; Talukdar, Akshay; Das, Anjan; Kumari, Khushboo; Dash, Prasanta K.; Chinnusamy, Viswanathan; Munshi, Anilabha Das; Behera, Tusar Kanti; Dey, Shyam Sundar (Frontiers in Plant Science, 2023)
Cucumber is an important vegetable crop grown worldwide and highly sensitive to prevailing temperature condition. The physiological, biochemical and molecular basis of high temperature stress tolerance is poorly understood in this model vegetable crop. In the present study, a set of genotypes with contrasting response under two different temperature stress were evaluated for important physiological and biochemical traits. Besides, expression of the important HSPs, AQPs, photosynthesis related genes was conducted in two selected contrasting genotypes at different stress conditions. It was established that high chlorophyll retention, stable membrane stability index, higher retention of water content, stability in net photosynthesis, high stomatal conductance and transpiration in combination with less canopy temperatures were the key physiological traits associated with heat tolerance in cucumber. Accumulation of biochemicals like proline, protein and antioxidants like SOD, catalase and peroxidase was the underlying biochemical mechanisms for high temperature tolerance. Upregulation of photosynthesis related genes, signal transduction genes and heat responsive genes (HSPs) in tolerant genotypes indicate the molecular network associated with heat tolerance in cucumber. Among the HSPs higher accumulation of HSP70 and HSP90 were recorded in the tolerant genotype, WBC-13 under heat stress condition indicating their critical role. Besides, Rubisco S, Rubisco L and CsTIP1b were upregulated in the tolerant genotypes under heat stress condition. Therefore, the HSPs in combination with photosynthetic and aquaporin genes were the underlying molecular network for heat stress tolerance in cucumber. The findings of the present study also indicated negative feedback of G-protein alpha unit and oxygen evolving complex in relation to heat stress tolerance in cucumber. These results indicate that the thermotolerant cucumber genotypes enhanced physio-biochemical and molecular adaptation under high-temperature stress condition. This study provides the foundation to design climate smart genotypes in cucumber through integration of favourable physio-biochemical traits and understanding the detailed molecular network associated with heat stress tolerance in cucumber.